Brexit and Parliament: The Anatomy of a Perfect Storm. Issue 2 (11th June 2020) - Russell, Meg
Abstract: The Westminster parliament lies at the heart of UK democracy. Yet its role and powers became increasingly controversial during the 'Brexit' process, following the 2016 referendum decision to leave the European Union. Fierce arguments were framed as 'parliament versus people', which fed a populist narrative and raised fundamental questions about where UK sovereignty should lie. This article charts the stages of parliament's Brexit 'perfect storm', tracing its causes to four factors: the design of the referendum, a period of (unfamiliar) minority government, deeply divided political parties, and the weakness of parliamentary rules in facilitating a solution. In the end, the Brexit argument was primarily one inside the Conservative Party, but parliament got the blame.